ISLAMIC SPIRITUALITY: REFLECTIONS ON CONTEMPORARY DA'WAH ISSUES - Ahmad Yuzki Faridian Nawafi (Universitas Islam Negeri (UIN) Mataram, 2024)
Islam is a da'wah religion, a religion that has a high religious side. Islamic da'wah has enjoyed various eras, from classic to contemporary, producing various da'wah methods and strategies. Rumors of contemporary da'wah have been heard, giving rise to various Muslim intellectual figures at home and abroad. This study aims to understand the concept of contemporary da'wah and the decadence of spirituality of contemporary Muslims. This research method uses a qualitative descriptive approach; the case is contemporary preaching and Muslim spirituality. The results of this study show that the da'wah in the contemporary era makes preachers more flexible in conveying da'wah messages, and the methods used get a variety of media. It is easier for Mad'u to access and receive da'wah messages whenever and wherever Mad'u is. However, this causes Muslim spirituality to decline.